Decriminalizing Marijuana Use as an Alternative Medical Treatment - Guntara, Bima; Sambas, Nandang; Yanto, Oksidelfa (Yayasan Sinergi Kawula Muda, 2024)
The discourse surrounding the legalization of Class I narcotics, particularly marijuana (Cannabis Sativa), as one of the alternative medical treatments, has been continuously debated for the past few years. Various studies have been advancing with technological progress, prompting some other countries to start legalizing marijuana for medical purposes with certain restrictions. In Indonesia, there is a clear law, namely Law Number 35 of 2009 concerning Narcotics, which imposes restrictions and prohibitions on the use of various narcotics. Violators of these regulations are subject to criminal sanctions. In this legal research, the author will conduct a literature study using a statutory approach, which involves examining all relevant laws and legal regulations related to narcotics and the legality of the policy on the use of Class I narcotics as alternative medical treatments, such as the 1945 Constitution of the Republic of Indonesia (UUD 45), Law Number 35 of 2009 concerning Narcotics, Law Number 17 of 2023 concerning Health, and Law Number 39 of 1999 concerning Human Rights. The research findings indicate that juridically, the Narcotics Law, especially Article 6 paragraph (1) letter a and Article 8 paragraph (1), prohibits the use of Class I narcotics for medical purposes, which is clearly contradictory to Article 28C paragraph (1) of the 1945 Constitution where every person has the right to develop themselves through the fulfillment of their basic needs, the right to education, and to benefit from science and technology, arts, and culture, for the purpose of improving their quality of life and the welfare of humanity. Furthermore, the Health Law does not specifically regulate the use of marijuana for medical purposes, but only addresses general regulations regarding the use of narcotics. It is hoped that the results of this research can become a reference for policy makers to legalize the use of marijuana as an alternative treatment.